Frontal EEG asymmetry as predictor of physiological responses to aversive memories. (30th April 2014) - Meyer, Thomas; Quaedflieg, Conny W. E. M.; Giesbrecht, Timo; Meijer, Ewout H.; Abiad, Schahrasad; Smeets, Tom
Abstract Evidence suggests that asymmetry in frontal electrical activity predicts responses to aversive experiences, such that higher left‐sided activity might dampen responses to trauma reminders. We measured frontal asymmetry at rest and during viewing of a trauma film, and assessed startle responses to film‐reminder images. To explore potential moderators, we compared two films (Study 1; N = 64) and modulated reappraisal (Study 2; N = 72). As expected, left frontal activation during film viewing predicted dampened responses in individuals who viewed a staged road accident. However, this effect tended to be reversed when a genocide documentary was used. In Study 2, all participants viewed the genocide film. Left frontal activity at rest again predicted higher startle responses, while reappraisal did not moderate the effects. Thus, the type of trauma film plays a crucial role in the effects of frontal asymmetry, which warrants further critical investigation.